Cardiac Manifestations of Antiphospholipid Syndrome: Clinical Presentation, Role of Cardiac Imaging, and Treatment Strategies - Tufano, Antonella; Di Minno, Matteo Nicola Dario; Guida, Anna; Lembo, Maria; Di Minno, Giovanni; Galderisi, Maurizio (Seminars in Thrombosis and Hemostasis, 2019)
Antiphospholipid syndrome (APS) is an autoimmune disorder characterized by the presence of antiphospholipid antibodies, vascular thrombosis (venous, arterial, or small vessels), and/or pregnancy morbidity. Diagnosis of APS is based on the presence of at least one clinical criterion (thrombotic events or pregnancy morbidity) and at least one of the laboratory criteria (persistently medium/high titer immunoglobulin G [IgG]/immunoglobulin M [IgM] anticardiolipin antibodies, and/or medium/high titer IgG/IgM anti-β2-glycoprotein I antibodies, and/or a positive lupus anticoagulant test), confirmed after repetition at least 12 weeks apart. The clinical spectrum of APS encompasses additional (extracriteria) clinical manifestations, including cardiac diseases. Heart involvement may become evident as a consequence of direct (autoimmune-mediated) or indirect (thrombosis) mechanisms, and include valve heart disease (vegetations and/or thickening associated with functional abnormalities) and intracardiac thrombosis, coronary, and vascular accelerated atherosclerosis, along with ischemic heart disease. APS can also cause pulmonary arterial hypertension, left ventricular dysfunction, and heart failure. This review describes the major cardiac manifestations of APS and illustrates the role of cardiac imaging for diagnosing subclinical and overt heart involvement and addressing management of these patients. The possible role of therapeutic strategies in cardiac manifestations of APS is also discussed.
Keywords: antiphospholipid syndrome; atherosclerosis; thrombotic event; antiphospholipid antibodies; echocardiography